SUMBER BELAJAR DAN BAHAN AJAR ILMU PENGETAHUAN SOSIAL (IPS) DI TINGKAT SEKOLAH DASAR - Fadila nur Zakina; Muhammad Nawir; Nevianti; Hamdia Sayyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social Studies (IPS) is a subject that plays an important role in developing elementary school students’ knowledge, attitudes, and social skills so that they are able to understand social realities and actively participate in social life. However, Social Studies learning still frequently encounters problems related to the limited use of diverse and contextual learning resources and teaching materials, causing learning activities to rely heavily on textbooks and to be less connected to students’ real-life experiences. This study aims to examine learning resources and teaching materials in elementary Social Studies learning, including their definitions, types, utilization, and the differences between learning resources and teaching materials in supporting the learning process. The method employed is a literature review by analyzing various relevant books and journal articles. The findings indicate that the use of diverse learning resources and systematically developed, contextual teaching materials can improve the quality of Social Studies learning, making it more effective and meaningful. Therefore, optimizing learning resources and developing teaching materials that align with students’ characteristics are essential to enhancing the quality of SocialStudies learning in elementary schools.